POLA PERMUKIMAN GUA-GUA DI KAKI GUNUNG WATANGAN: SUATU HIPOTESIS PERMUKIMAN GUA KAWASAN TIMUR JAWA - Indah Asikin Nurani (Berkala Arkeologi, 1995)
The way of life in caves in Indonesia occurred during the Post-Plestocene (early Holocene) period, which in prehistoric terms belongs to the period of hunting and gathering food. At this time the cave or rock shelter served as a shelter and a place to carry out daily activities. In maintaining their life, humans at that time still depended on the natural environment around them, which was an adaptative step in managing and using available natural resources. The exploitation of the ecological potential by humans is influenced by the level of technology and human "intelligence" in processing natural resources around it.